The Influence of Employee Training and Implementation of Company Operational Procedure Standards on Improving Employee Performance in Prima Freshmart Bogor City - Ningsih, Rosmalia; Udriyah; Ridho, Ali (International Publisher (YAPENBI), 2024)
Human resources are the most important asset in an organization, and an important factor in employee performance plays an important role in optimizing their contribution. Companies need training programs and an understanding of SOPs so they tend to be better prepared to carry out their duties. In this case, the Company's target was not achieved and the Company assessed that employee performance had decreased. This research aims to measure the significant influence of training and implementation of SOPs on the performance of Prima Freshmart employees. The results of hypothesis testing and multiple linear regression show that employee training and implementation of SOPs have a positive and significant impact on improving employee performance at Prima Freshmart, Bogor City. The value of the Coefficient of Determination (Adj R2) is 0.826, which means that this indicates that the contribution of the independent variables, namely Employee Training and SOP, to the dependent variable, namely Employee Performance, is 82.6%, while the remaining 17.4% is influenced by other variables that have not yet been determined. researched or not included in the regression in this study.